THE ORIGIN OF SPORTS PSYCHOLOGY ITS DEVELOPMENT AND CURRENT STATE IN ARMENIA - Babayan , H. A. (Արդի հոգեբանություն, 2025)
The article considers the issues of formation and development sports psychology in Armenia. They are due to the foundation of the Armenian State Institute of Physical Culture and Sport and the formation of the dep. Of Sports Pedagogy and Psychology, as well as to the long-term and fruitful academic, scientific and methodical works of the department staff. Achievements and prospects of the development of Sports Psychology in Armenia are presented in accordance with the description. Of the academic and scientific work and the stages of its development.